Wisata Sejarah, Warisan Budaya, dan E-Service: Study Kasus untuk Menilai Preferensi Pelaku Wisata Dimasa Pandemi Covid 19 di Yogyakarta - Duari, I Putu Hardani Hesti (Universitas Veteran Bangun Nusantara, 2021)
This paper discusses the use of in-depth FGDs to assess residents, tourists, and travelers' preferences for e-service electronic services that will increase access to historical tourism heritage and cultural tourism in Yogyakarta Special Region (Keraton Yogyakarta and Taman Sari) during the Covid Pandemic. 19. Several electronic e-services are mentioned, such as in social media FB, TW, IG and travel blogs. The implementation of this integration is closely related to information and communication technology (ICT). The results show that the need for customized information e-service services, profiling, booking systems, trip planner, guided tours, online practical information (transportation schedules, etc.) as well as virtual tours. In several findings, the FGD group expressed the need for various forms of electronic governance. Cellular devices and navigation systems are also high on the agenda in more technologically advanced cities.